Transformational leadership, organisational climate, and internal locus of control on innovative work behaviour in hospitality sector of rural area - Rizq Adyatama Byantara; Ika Nurul Qamari; Mohd Shamsuri Md Saad (Universitas Negeri Surabaya, Indonesia, 2023)
Studying innovative work behaviour in the Industrial Age 4.0 is an interesting research issue. Using an internal locus of control as a moderator, this study seeks to understand how transformational leadership and organisational climate might promote innovative work behaviour. One hundred and twenty-five respondents participated in this quantitative research, where they were selected based on a purposive sampling method. A cross-sectional survey was conducted to collect the data utilising established instruments looking into the perspectives of the respondents about transformational leadership, organisational climate, innovative work behaviour, and internal locus of control. Data analyses were conducted using SPSS 24 version, where descriptive and inferential analyses, multiple linear analysis and moderated regression analysis (MRA) were undertaken. Based on the analysis, the study's results showed that transformational leadership has a negative and small impact on innovative work behaviour. Organisational climate and internal locus of control were found to positively and moderately impact innovative work behaviour. However, the internal locus of control is needed to moderate the impact of transformational leadership on innovative work behaviour. Based on these results, the hotel industry needs to consider transformational leadership attitudes to create innovative behaviour in human resources, especially in this industry. In addition, it is hoped that future research in this area can be focused on different types of job and gender to produce even better results.